Mathematical Models of Effective Topology of Computer Networks for Electric Power Supply Control on Railway Transport - Oleksandr Stasiuk; Valeriy Kuznetsov; Vitalii Zubok; Lidiya Goncharova; Antonina Muntian (Communications - Scientific letters of the University of Zilina, 2022)
The paper is devoted to analysis of modern directions of innovation-investment formation of intelligent computer networks that control the fast-moving technological processes of electricity supply. It is based on the conclusion that the problem of increasing the productivity of information exchange between information resources and consumers is dominant. A method for increasing the efficiency of information exchange is proposed as a search for the rational location of a new node and the organization of such a set of its connections among the whole set of nodes of the computer network, which provides a minimum average topological distance. Mathematical models of effective topological organization of connections in computer network of power consumption control at the level of traction substations, electric power distances and the railway in general are proposed.